TINJAUAN ASPEK HUKUM TERHADAP LARANGAN MEMBERIKAN SEJUMLAH UANG ATAU BARANG KEPADA GELANDANGAN DAN PENGEMIS - Abd. Rachman A. Latif (SASI, 2017)
By juridical any person or legal entity is prohibited to give any money or goods to beggars and homeless. This prohibition is governed by the laws and regulations. Judging from the legal philosophy, the local regulation imposed by the local government on the prohibition of giving money or goods to homeless and beggars is the right step, because in essence the law is made is to regulate, protect and prosper the community. Government efforts in tackling homeless and beggars are done with preventive efforts, repressive efforts and rehabilitative efforts. This effort is aimed at getting homeless and beggars to re-run their social functions.